2018
DOI: 10.1007/s10712-018-9486-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Spectroscopy of Urban Environments

Abstract: Future spaceborne imaging spectroscopy data will offer new possibilities for mapping ecosystems globally, including urban environments. The high spectral information content of such data is expected to improve accuracies and thematic detail of maps on urban composition and urban environmental condition. This way, urgently needed information for environmental models will be provided, for example, for microclimate or hydrological models. The diverse vertical structures, highly frequent spatial change and a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 95 publications
(140 reference statements)
0
12
0
Order By: Relevance
“…Khatami et al, 2016;Wulder et al, 2018) and vegetation characterization (e.g. Verrelst et al, 2015). As the PALM model requires high spatial resolution for performing building-resolving simulations, the free and open Sentinel-2 satellite data are of interest as well as the data of commercial satellite constellations like Rapid Eye or World View.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Khatami et al, 2016;Wulder et al, 2018) and vegetation characterization (e.g. Verrelst et al, 2015). As the PALM model requires high spatial resolution for performing building-resolving simulations, the free and open Sentinel-2 satellite data are of interest as well as the data of commercial satellite constellations like Rapid Eye or World View.…”
Section: Data Sourcesmentioning
confidence: 99%
“…This is specifically challenging when mapping infrastructure and the LC composition of smaller settlements and in rural areas. Even though increased spatial resolution can partly counter this problem, van der Linden et al (2018) found that at 9 m spatial resolution, 80% of the pixels still contained two or more surface types. Moreover, mapping the type and characteristics of settlements also requires knowledge about less abundant LC components, including different vegetation types ( Wentz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of imaging spectroscopy (IS) compared to multispectral imagery has opened the way to providing access to more physical surface properties for better monitoring of land cover mapping, vegetation, and soil monitoring in both urban and natural ecosystems [1][2][3]. However, their derivation requires accurate surface reflectance retrieval.…”
Section: Introductionmentioning
confidence: 99%